Polyblend Nanofibers to Regenerate Gingival Tissue: A Preliminary In Vitro Study - Canciani, Elena; Gagliano, Nicoletta; Paino, Francesca; Amler, Evžen; Divin, Radek; Denti, Luca; Henin, Dolaji; Fiorati, Andrea; Dellavia, Claudia (Frontiers in Materials, 2021)
AIM: The regeneration of small periodontal defects has been considered an important and challenging issue for dental practitioners. The aim of this preliminary in vitro study was to analyze the effects of polycaprolactone (PCL) nanofibers enriched with hyaluronic acid and vitamin E vs. nude nanofibers on gingival fibroblasts activity, an innovative graft for periodontal soft tissue regeneration purposes. METHODS: Nanofibers were produced in PCL (NF) or PCL enriched with hyaluronic acid and vitamin E (NFE) by electrospinning technique. NF and NFE were stereologically and morphologically characterized by scanning electron microscope (SEM), and composition was analyzed by infrared spectroscopy. Human fibroblasts were obtained from gingival tissue fragments (HGF) and then seeded on NF, NFE and plastic (CT). Cell adhesion and morphology were evaluated using SEM at 24 hours, cell viability after 24, 48 and 72 hours by Alamar Blue® assay. Gene expression for COL I, LH2b, TIMP-1, PAX and VNC was analyzed by real-time RT-PCR in samples run in triplicate and GAPDH was used as housekeeping gene. Slot blot analysis was performed and immunoreactive bands were revealed for MMP-1, COL-I. YAP and pYAP were analyzed by Western blot and membranes were reprobed by α-tubulin. Statistical analysis was performed. RESULTS: Diameter of NFE was increased by 30% compared with NF. IR spectrum revealed the presence of PCL. At 24 hours HGF adhered on NF and NFE conserving fibroblast-like morphology. At 72 hours from seeding, statistically significant differences were found in proliferation of HGF cultured on NF compared to NFE. Expression of genes (LH2b, TIMP-1, MMP-1) and proteins (COL I) related to collagen turnover revealed a reduction of COL-1 secretion in cells cultured on NF and NFE compared to CT, however NFE stimulated cross-linked collagen deposition. Mechanosensor genes (PAX, VNC, YAP) were upregulated in HGF on NF while they were decreased in cells grown on NFE. CONCLUSION: Preliminary data suggest that PCL enriched nanofibers could represent a support to induce HGF proliferation, adhesion, collagen cross-linking and to reduce collagen degradation, therefore favoring collagen deposition in gingival connective tissue.